2018
DOI: 10.1002/cncr.31573
|View full text |Cite
|
Sign up to set email alerts
|

Variation in prostate cancer treatment and spending among Medicare shared savings program accountable care organizations

Abstract: ACOs vary widely in treatment, potential overtreatment, and spending for prostate cancer. ACOs with stronger urologist engagement are less likely to treat men with a high risk of noncancer mortality, and this suggests that organizations that better engage specialists may be able to improve the value of specialty care. Cancer 2018. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…For advanced PCa, more aggressive treatment measures are taken, represented by androgen deprivation therapy (ADT) for metastatic PCa and docetaxel and prednisolone for castration-resistant PCa (25,26). Potential side effects from treatment may be one of the reasons for this phenomenon (27,28). The spectrum of cause of death also changed more significantly with increased follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…For advanced PCa, more aggressive treatment measures are taken, represented by androgen deprivation therapy (ADT) for metastatic PCa and docetaxel and prednisolone for castration-resistant PCa (25,26). Potential side effects from treatment may be one of the reasons for this phenomenon (27,28). The spectrum of cause of death also changed more significantly with increased follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Modi et al reported that stronger engagement of urologists in accountable care organizations was associated with a lower likelihood of potential overtreatment (odds ratio: .29; 95% confidence interval: .10-.86) in the US. 34 Shi et al compared the cost-effectiveness of 6 common cancers from a priority setting perspective. Their preliminary analysis suggested that stomach cancer and colorectal cancer were the most cost-effective target cancers, and they concluded that they can be prioritized in future scaled-up screening in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kuipers et al investigated the relationship between mass media campaigns for smoking cessation and the success rate of quit attempts, and found that an increase in mass media expenditure of 10% of the monthly average was associated with a 0.51% increase in success rates of quit attempts (95% CI 0.10-0.91%) [30]. Holleman et al evaluated the impact of alternative risk-sharing arrangements (RSAs) for non-small cell lung cancer therapies based on real-world data and concluded that RSAs can mitigate uncertainty around the incremental cost-effectiveness or budget impact of drugs [31]. Modi et al reported that stronger engagement of urologists in accountable care organizations was associated with a lower likelihood of potential overtreatment (odds ratio: 0.29; 95% con dence interval: 0.10-0.86) in the US [32].…”
Section: Discussionmentioning
confidence: 99%